Implementing and Evaluating the Performance Metrics using Energy Consumption Protocols in MANETs using Multi-Path Routing- Fitness Function - P, Mounika; Kumar, Prasanna M (International Journal of Computer Sciences and Engineering, 2025)
The energy consumption plays a key role in Mobile Adhoc Network in a day to day life. Mobile Ad Hoc Network (MANET) structure is a temporary network organized dynamically with a possible set of wireless mobile nodes without depending on extra any infrastructural facilities and central administration requirements additionally based on the solutions to overcome the minimal energy consumption issues. Nodes are battery operated temporarily does not operated on permanent batteries, so energy consumed by a battery depends on the lifetime of the battery and its energy utilization dynamically decreases as the nodes change their position in MANETs. Multi-path routing algorithm in MANETs provides a best optimal; solution to transmit the information in multiple paths to minimize the end to end delay, reduce energy consumption and also increases life time of the network. The research mainly focused on minimum energy consumption techniques in MANET is of a great challenge in industries. In this paper, the author highlights a novel approach Adhoc on Demand Multipath Distance Vector (AOMDV) routing protocol to minimize energy consumption algorithm in MANET by incorporating the demand multipath distance and fitness function. The Adhoc on Demand Multipath Distance Vector-Fitness Function (AOMDV-FF) routing protocol short out the path that consumes minimum energy and the simulation performance is evaluated using network simulator 2 (NS2)tool. Two protocols are proposed in this work AOMDV and AOMDV-FF and compared their performance parameters such as energy consumption, throughput, packet delivery ratio, end to end delay, network life time and routing overhead in terms of speed, packet size and simulation time. The overall simulation results of the proposed AOMDV-FF method is considered a network with 49 nodes and the network performance factor-end to end delay 14.4358x10-3 sec, energy consumption 18.3673 joules, packet delivery ratio 0.9911 and routing overhead ratio 4.68 are evaluated the results show an improvement as compared to other methods AOMDV and AOMR-LM.